Blogs and the Promotion and Tenure Letter - Ellen S. Podgor (Washington University Law Review, 2006)
Writing promotion and tenure letters is an important service to the academy, albeit one that is seldom rewarded in comparison to the enormous time consumption involved. And although evaluations to date have all been premised on hard-text material, it is likely that soon the day will come that the packet of scholarship material arriving on one's doorstep will be a Website address that leads to a blog. In thinking about whether law blogs are legal scholarship, an important consideration in answering this question is how a blog should be evaluated for promotion and tenure purposes.
Keywords: Blogs; Law – Study & amp; teaching; Academic tenure; legal literature; United States